Principal Strategies for Strengthening Teachers’ Professional Competence in PAUD: Strategi Utama untuk Meningkatkan Kompetensi Profesional Guru di PAUD - Umiyati, Siti; Nadiyah, Nadiyah; Wati, Mastika; Astria, Rani; Wati, Evi Sulistia (Indonesian Journal of Education Methods Development, 2023)
General Background: Teachers’ professional competence is a key determinant of education quality, particularly at the early childhood level. Specific Background: Principals play a pivotal role in designing and implementing strategies to foster teachers’ competence in lesson planning, classroom management, and innovative teaching practices. Knowledge Gap: While many studies have examined teacher development, limited research has explored principals’ systematic strategies in the context of community-based PAUD institutions. Aim: This study aims to describe the strategies implemented by the principal of PAUD Sejenis Pelita Bunda Muaro Jambi to improve teachers’ professional competence. Results: Using a descriptive qualitative approach with observation, interviews, and documentation, the findings reveal that five main strategies—academic supervision, internal workshops, teacher learning communities, motivation and appreciation, and performance evaluation—significantly supported teacher development. Additional initiatives such as literacy culture, digital learning, and benchmarking enriched teachers’ professional growth, with 80% of teachers reporting improved ability to design lesson plans (RPPH). Novelty: This study highlights the integration of formal and informal strategies, combining supervision with collaborative and motivational practices. Implications: The findings emphasize the importance of principals’ adaptive leadership in sustaining teacher professionalism and can serve as a model for early childhood institutions seeking to strengthen teaching quality. Highlights: Principals integrate supervision, training, and evaluation Collaborative communities foster teacher professional growth Literacy, technology, and benchmarking enrich competence Keywords: Principal Strategy, Professional Competence, Teacher Development, PAUD, Leadership